Generation of cDC-like cells from human induced pluripotent stem cells via Notch signaling. Issue 1 (31st January 2022) - Makino, Kenichi; Long, Mark D; Kajihara, Ryutaro; Matsueda, Satoko; Oba, Takaaki; Kanehira, Kazunori; Liu, Song; Ito, Fumito
Abstract : Background: Dendritic cells (DCs) play critical roles in regulating the innate and adaptive immune responses, and have long been a major focus of cancer immunotherapy. Accumulating evidence suggests that conventional type 1 DCs (cDC1s) excel in cross-presentation of exogenous antigens on MHC-I molecules and induction of antitumor CD8 + T cell immunity; however, obtaining large numbers of cDC1s is difficult. The use of reprogramming and differentiation technology is advantageous for obtaining unlimited numbers of autologous cDC1s especially for therapeutic interventions where repeated vaccinations are required. However, generation of cDC1s from human induced pluripotent stem cells (iPSCs) remains elusive. Methods: Human iPSCs established from peripheral blood T cells and monocytes were differentiated to myeloid cells under on-feeder or feeder-free culture conditions in vitro. Phenotype, genomic and transcriptomic signature, and function of human iPSC-derived DCs were analyzed. The role of Notch signaling for the generation of HLA-DR + cells from human iPSCs was interrogated by a loss- and gain-of-function approach. Results: Flow cytometric analyses and single-cell profiling of HLA-DR + cells revealed that human iPSCs gave rise to CD141 + XCR1 + CLEC9A + cells (cDC1s), CLEC4A hi CLEC10A – CD1c + cells (cDC2As), CLEC4A lo CLEC10A + CD1c + cells (cDC2Bs), CD163 – CD5 + CD1c + cells (CD5 + cDC2s), and AXL + SIGLEC6 + cells (AS-DCs) on OP9 feeder cells expressing the Notch ligand delta-like 1 (OP9-DL1) while the majority of iPSC-derived cells differentiated on OP9 cells were CD163 + CD5 – CD1c + cells (DC3s) and monocytes. Plasmacytoid DCs were not differentiated from iPSCs on either OP9 or OP9-DL1 cells. Inhibition of Notch signaling during co-culture of iPSC-derived CD34 + hematopoietic progenitor cells with OP9-DL1 cells abrogated generation of cDC1s, cDC2As, cDC2Bs, CD5 + cDC2s, and AS-DCs but increased frequency of DC3s. Notch-activated human iPSC-derived XCR1 + CLEC9A + HLA-DR + CD11c + cells exhibited similar gene expression profile with peripheral blood cDC1s. Human iPSC-derived DCs have phagocytic, T-cell proliferative, and cytokine-producing functions. Conclusions: Our study demonstrates a critical role of Notch signaling in regulating developmental pathway of human cDCs. These findings provide insights into the future development of personalized treatment with unlimited numbers of autologous cDCs from human iPSCs.